MASIH TEPATKAH ROA SEBAGAI PENGUKURAN KINERJA KEUANGAN INDUSTRI ASURANSI DI INDONESIA? - Oyo Sukarya; Farah Margaretha (Lembaga Penerbit Fakultas Ekonomi dan Bisnis, 2018)
The problem of this research was the determinants of financial performance in insurance company in indonesia, both of internal and external factor. There are some factors that influence positively and the other side influences negatively on the financial performance. The objectives of this research was to examine the factors that affect the financial performance of insurance companies in Indonesia, which was viewed from profitability. The methodology of this research was multiple regression. The object of research is 64 insurance companies listed in Otoritas Jasa Keuangan (OJK) period 2011-2015. Finding and contribution in this research showed that leverage, equity, and management competence index proved to have a significant positive influence, on size, ownership and age, and they were proved to have a significant negative effect on retention ratio had a non-significant positive effect, and Underwriting Risk negatively influenced insignificantly into financial performace (ROA). Implication in this research was that companies need to monitor the fluctuation of leverage and Equity, that positively influence the financial performance, where leverage depends on ratio of debt to equity. In addition assets and ownership negatively affect financial performance, in order to monitor the iincrease in line with the profit increase.